Vitamin B12 Deficiency in Type 2 Diabetes Mellitus - Bello, Carlos Tavares (2017)
Introduction: Type 2 diabetes mellitus is a common disease, affecting up to 13.1% of the Portuguese population. In addition to the known micro and macrovascular complications, drug side effects constitute a major concern, leading to changes in the treatment guidelines, which favor safety over efficacy. Metformin is the first-line pharmacological treatment for most patients with type 2 diabetes mellitus; however, it has been associated with vitamin B12 deficiency in up to 30% of treated patients. The authors describe the prevalence of vitamin B12 deficiency in a diabetic population and explore the possible underlying factors.Material and Methods: Retrospective, observational study. Clinical and laboratory data of type 2 diabetes mellitus patients whose vitamin B12 status was evaluated in the last decade (2005 - 2016) were analyzed. Patients with known malabsorptive syndromes or having undergone bariatric surgery were excluded from the study. Statistical analysis of the data was done and the results were considered statistically significant at p values < 0.05.Results: The study included a total of 1007 patients (58% women) with a mean age of 66.4 ± 12.2 years and 11 ± 10.4 years of type 2 diabetes mellitus duration. These patients had a high prevalence of complications: diabetic renal disease 47.7%, neuropathy 9.2%, retinopathy 14.9%, coronary artery disease 8.4%, cerebrovascular disease 10.9%, and peripheral arterial disease 5.5%. Vitamin B12 deficiency (< 174 ng / dL) was present in 21.4% of the population and this subgroup was older (68.4 vs 65.8 years, p = 0.006), had a longer type 2 diabetes mellitus duration (13.35 vs 10.36 years; p = 0.001), higher prevalence of retinopathy (20.9% vs 13.3%; p = 0.005) and thyroid dysfunction (34% vs 23.7%; p = 0.002). Vitamin B12 deficiency was also more frequent in patients treated with metformin (24.7% vs 15.8%; p = 0.017), antiplatelet agents (25.4% vs 16.2%, p < 0.001), and calcium channel blockers (26.8% vs 18.2%; p = 0.001). After adjustment for possible confounders, the variables associated with B12 deficiency were: metformin, hypothyroidism, age and type 2 diabetes mellitus duration.Discussion: Despite the retrospective design, the results report a high prevalence of vitamin B12 deficiency in the type 2 diabetic population. This study also demonstrates that the B12 deficiency risk is higher in older people, with longer diabetes mellitus duration, hypothyroidism and treated with metformin.Conclusion: Further studies are needed to identify the risk factors for the B12 deficit. The recognition of these variables will contribute to optimize the screening and prevention of the B12 deficiency in type 2 diabetes mellitus.